Предмет: Алгебра,
автор: ксюшатукмачёва
помогите решить пожалуйста
(3х-1)(4х+6)=2(6х-3)
Ответы
Автор ответа:
0
(3х-1)(4х+6)=2(6х-3),
12х²+18х-4х-6=12х-6,
12х²+18х-4х=12х,
12х²+14х=12х,
12х²+14х-12х=0,
2х(6х+7-6)=0,
2х(6х+1)+0,
х(6х+1)=0,
6х+1=0, x=0.
х= .
Ответ: ; 0.
12х²+18х-4х-6=12х-6,
12х²+18х-4х=12х,
12х²+14х=12х,
12х²+14х-12х=0,
2х(6х+7-6)=0,
2х(6х+1)+0,
х(6х+1)=0,
6х+1=0, x=0.
х= .
Ответ: ; 0.
Автор ответа:
0
спасибо огромное
Похожие вопросы
Предмет: Английский язык,
автор: gamzatkyzydiana
Предмет: Биология,
автор: balgabekovadilyara
Предмет: Английский язык,
автор: aaulymmuratbekova80
Предмет: Физика,
автор: skywars
Предмет: Математика,
автор: Natalifas